Modelling the effectiveness of using online food delivery services apps among customers in Klang valley during Covid-19 pendamics / Prof Madya. Dr Rozita Naina Mohamed ... [et al.] - Mohamed, Rozita Naina (Prof Madya. Dr); Rusli, Mohd Saifullah; Borhan, Halimahton (Prof Madya. Dr.) (2021)
Online services of food delivery are more critical than ever. It has become more and more popular worldwide. Customers are getting comfortable using the apps for services to order the meals they want via their smartphone using the apps. There are more than ten online food distribution service providers currently operating on the market in Malaysia. What separates them, though, is the speed of services, the food prices, the delivery rates, the selections offered and deals, the user interface(UI) of the apps, user friendliness etc. This research is therefore carried out to examine the key factors affecting the intention of customers to use online food delivery services among customers in the Klang Valley during Covid-19 in 2020. The research investigating the most significant factors that influence the customer purchase intention on using Online Food Delivery (OFD) services. There are 4 independent variables which we are focusing on; time, price factor, convenience motivation factor and food illustration. From the research, we have found out that convenience motivation factor is the most important exogenous variable that can influence purchase intention directly, sequentially through shopping motivations. Customers wants the transaction to be quick, easy, convenience and simple. The other factors that have significant impact to customer’s purchase intentions are price and time factor. The least factor that influence customer’s purchase intention is the food illustrations. The study is carried out by gathering responses from over 207 people and only 167 participants are eligible for inclusion.